2012
DOI: 10.1128/jb.06040-11
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Scale Metabolic Reconstruction and Hypothesis Testing in the Methanogenic Archaeon Methanosarcina acetivorans C2A

Abstract: Methanosarcina acetivorans strain C2A is a marine methanogenic archaeon notable for its substrate utilization, genetic tractability, and novel energy conservation mechanisms. To help probe the phenotypic implications of this organism's unique metabolism, we have constructed and manually curated a genome-scale metabolic model of M. acetivorans, iMB745, which accounts for 745 of the 4,540 predicted protein-coding genes (16%) in the M. acetivorans genome. The reconstruction effort has identified key knowledge gap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 76 publications
2
62
0
Order By: Relevance
“…This exciting progress allowed the unraveling of protein function in vivo and qualifies Archaea as model organisms for synthetic biology and systems biology (303,397,398). Thus, within the last years, the first genome-wide metabolic models, flux balance analysis (FBA), as well as first detailed reaction kinetic models were established for Archaea (338,(399)(400)(401)(402)(403)(404). These studies also analyzed the responses to different carbon sources and, often performed in combination with biochemical studies, revealed new, exciting, deeper insights into the regulation of metabolic networks at the transcript and protein levels.…”
Section: Metabolic and Regulatory Characteristics Of Well-studied Arcmentioning
confidence: 99%
“…This exciting progress allowed the unraveling of protein function in vivo and qualifies Archaea as model organisms for synthetic biology and systems biology (303,397,398). Thus, within the last years, the first genome-wide metabolic models, flux balance analysis (FBA), as well as first detailed reaction kinetic models were established for Archaea (338,(399)(400)(401)(402)(403)(404). These studies also analyzed the responses to different carbon sources and, often performed in combination with biochemical studies, revealed new, exciting, deeper insights into the regulation of metabolic networks at the transcript and protein levels.…”
Section: Metabolic and Regulatory Characteristics Of Well-studied Arcmentioning
confidence: 99%
“…This is a rather high percentage, eclipsing that of the previous M. maripaludis reconstruction (81.4%) (27) and comparing favorably to reconstructions of fellow methanogens Methanosarcina barkeri and Methanosarcina acetivorans (85.7% and 85.1%, respectively) (55, 56). We suspect that a major reason for this high percentage of gene-associated reactions was our use of likelihood-based gap filling (29), which resulted in the automated addition of 66 genes to our reconstruction before manual curation.…”
Section: Resultsmentioning
confidence: 65%
“…Of the 201, 211 and 645 differentially expressed genes identified, about half were associated with reactions in our genome-scale metabolic models for M. acetivorans [48, 49] (affecting 149, 110, 359 total reactions, respectively). Genes associated with energy metabolism account for only 8–18% of all DEG depending on compared substrates (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We updated the genome-scale metabolic reconstruction i MB745 [48] by incorporating newly characterized pathways and gene:reaction mappings. Several additional model improvements dealt with amino acid synthesis and ligation (e.g.…”
Section: Resultsmentioning
confidence: 99%